Repeasantization of the future. The peasant as an alternative to the collapse of the global agri-food system - Contreras Román, Raúl (2021)
Deagrarianization and depeasantization have been the dominant trends in the agrarian history of neoliberal capitalism. These phenomena have been inherent to the installation of a global agri-food system, supported by agribusiness and corporate agribusiness. This system has shown numerous vulnerabilities, which were made evident during the international economic and food crisis unleashed in 2007. The COVID-19 pandemic has once again exposed the vulnerabilities of the corporate agri-food system, while it has narrowed its capacities to guarantee food security. Since its foundation, the international peasant movement grouped under Vía Campesina has opposed to the commodification of food and has struggled to place the farmer at the center of the discussion on food systems. The movement has proposed that the right to food can only be ensured by farmers, who, in turn, will be guarantors of Food Sovereignty. For this, advancing repeasantization is imperative, both quantitatively and qualitatively. Based on recent bibliography on the matter, this article presents the peasant option for repeasantization as an alternative to corporate and neoliberal control of food production and distribution and, more broadly, as a horizon for the construction of a future post-pandemic world.